Immune cells mediate the effects of gut microbiota on neuropathic pain: a Mendelian randomization study - Hao Pan; Cheng-xiao Liu; Hui-juan Zhu; Guang-fen Zhang (The Journal of Headache and Pain, 2024)
Abstract Background The gut microbiota may be involved in neuropathic pain. However, the causal association between gut microbiota and neuropathic pain remains unclear. Whether immune cells and inflammatory factors mediate the pathway from gut microbiota to neuropathic pain has not been elucidated. Methods We obtained the summary data of 412 gut microbiota, 731 immune cells, 91 inflammatory factors, and five types of neuropathic pain (drug-induced neuropathy, postherpetic neuralgia, sciatica, trigeminal neuralgia, and unspecified neuralgia) from large-scale genome-wide association study (GWAS) datasets and the FinnGen database. We used bidirectional Mendelian randomization (MR) analysis to explore the causal association between gut microbiota and neuropathic pain. Additionally, we conducted a mediation analysis to identify whether immune cells and inflammatory factors act as mediators within these causal relationships. Results Our study revealed 30 causal relationships between 26 gut bacterial taxa and five types of neuropathic pain, including four associated with drug-induced neuropathy, six with postherpetic neuralgia, five with sciatica, eight with trigeminal neuralgia, and seven with unspecified neuralgia. Moreover, we identified 35 gut bacterial pathway abundances causally involved in neuropathic pain. The reverse MR analysis showed no evidence of reverse causality from gut microbiota to neuropathic pain. Mediation analysis demonstrated that the immune cell phenotype “HLA-DR++ monocyte % leukocyte” mediated the causal relationship between p_Proteobacteria and sciatica with a mediation proportion of 36.15% (P = 0.038), whereas “CD11c on CD62L+ myeloid dendritic cell” mediated the causal pathway from assimilatory sulfate reduction to trigeminal neuralgia with a mediation proportion of 27.90% (P = 0.041). Conclusion This study identified the causal relationships between several specific gut microbiota and various neuropathic pain subtypes. Additionally, two immune cells may act as potential mediators in the pathways from gut microbiota to neuropathic pain.